An Assessment of Genetic Diversity and Drought Tolerance in Argan Tree (Argania spinosa) Populations: Potential for the Development of Improved Drought Tolerance - Chakhchar, Abdelghani; Haworth, Matthew; El Modafar, Cherkaoui; Lauteri, Marco; Mattioni, Claudia; Wahbi, Said; Centritto, Mauro (Frontiers in Plant Science, 2017)
The argan tree (Argania spinosa) occurs in a restricted area of Southwestern Morocco characterised by low water availability and high evapotranspirative demand. Despite the adaptation of the argan tree to drought stress, the extent of the argan forest has declined markedly due to increased aridity, land use changes and the expansion of olive cultivation. The oil of the argan seed is used for cooking and as the basis for numerous cosmetics. The identification of argan tree varieties with enhanced drought tolerance may minimise the economic losses associated with the decline of the argan forest and constrain the spread of desertification. In this study we collected argan ecotypes from four contrasting habitats and grew them under identical controlled environment conditions to investigate their response to drought. Leaf gas exchange analysis indicated that the argan ecotypes showed a high degree of adaptation to drought stress, maintaining photosynthetic activity at low levels of foliar water content and co-ordinating photosynthesis, stomatal behaviour and metabolism. The stomata of the argan trees were highly sensitive to increased leaf to air vapour pressure deficit, representing an adaptation to growth in an arid environment where potential evapotranspiration is high. However, despite originating in contrasting environments, the four argan ecotypes exhibited similar gas exchange characteristics under both fully irrigated and water deficit conditions. Population genetic analyses using microsatellite markers indicated a high degree of relatedness between the four ecotypes; indicative of both artificial selection and the transport of ecotypes between different provinces throughout centuries of management of the argan forest. The majority of genetic variation across the four populations (71%) was observed between individuals, suggesting that improvement of argan is possible. Phenotypic screening of physiological responses to drought may prove effective in identifying individuals and then developing varieties with enhanced drought tolerance to enable the maintenance of argan production as climate change results in more frequent and severe drought events in Northern Africa.